Terapi SEFT (Spiritual Emotional Freedom Technique) Sebagai Alternatif Mengatasi Kecemasan Pada Pembelajaran Praktik Klinik Kebidanan : Debby Syullelu Diyeni, Yustinus Joko Dwi Nugroho, Prilya Shanty Andrianie - Syullelu Diyeni, Debby; Joko Dwi Nugroho, Yustinus; Shanty Andrianie, Prilya (SOCIAL PHILANTHROPIC, 2024)
The aim of this research is to discover whether SEFT therapy can reduce students' anxiety levels. This experimental research was conducted on 52 fourth semester midwifery students, Sebelas Maret University, Surakarta who were categorized as moderate and severe anxiety. Random sampling was carried out on them to obtain a control group and an experimental group. The Mann-Whitney test showed there was no difference between the pretest in the control group and the pretest in the experimental group with p value = 0.599 > 0.05. Meanwhile, in the posttest, the value of p = 0.000 and follow-up p = 0.000 <0.05, meaning that there is a difference in the posttest and follow-up between the control group and the experimental group. The Wilcoxon test shows that the p value for the pretest and posttest in the experimental group = 0.000 and posttest with follow-up = 0.000 >< 0.05, meaning there is a difference between the pretest and posttest, as well as posttest and follow-up in the experimental group. On the other hand, in the control group, the p value in the pretest and posttest = 0.068 and posttest with follow up = 0.251 > 0.05, meaning there is no difference between pretest and posttest, or posttest and follow-up in the control group. It can be said that the anxiety level of the experimental group experienced a significant decrease after being given SEFT Therapy